Spatial fingerprint and magnitude of changes in the Atlantic meridional overturning circulation during marine isotope stage 3 - Zhang, Xiao; Prange, Matthias; Merkel, Ute; Schulz, Michael (Geophysical Research Letters, 2015)
Pronounced millennial-scale climate variability during marine isotope stage 3 (MIS3) is considered to be linked to changes in the state of the Atlantic meridional overturning circulation (AMOC), i.e., a warm interstadial/cold stadial state corresponds to a strong/weak AMOC. Based on a series of freshwater hosing/extraction experiments with the state-of-the-art Community Climate System Model version 3, we construct a global spatial fingerprint of oceanic temperature anomalies in response to AMOC changes under MIS3 boundary conditions. Highest sensitivity to AMOC changes, especially in summer, is found in northeastern North Atlantic sea surface temperature, but a characteristic temperature fingerprint is also found at subsurface levels. After testing significance of the linear sea surface temperature (SST)-AMOC regressions, the model results are combined with paleo-SST records to estimate the magnitude of millennial-scale Dansgaard-Oeschger AMOC variations during MIS3. The results suggest a mean difference in AMOC strength between interstadial and (non-Heinrich) stadial states of 9.21.2Sv (1 sigma).